2020
DOI: 10.1002/anie.201914728
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Vibrational Side of Spin‐Phonon Coupling in Single‐Molecule Magnets via 161Dy Nuclear Resonance Vibrational Spectroscopy

Abstract: Synchrotron‐based nuclear resonance vibrational spectroscopy (NRVS) using the Mössbauer isotope 161Dy has been employed for the first time to study the vibrational properties of a single‐molecule magnet (SMM) incorporating DyIII, namely [Dy(Cy3PO)2(H2O)5]Br3⋅2 (Cy3PO)⋅2 H2O ⋅2 EtOH. The experimental partial phonon density of states (pDOS), which includes all vibrational modes involving a displacement of the DyIII ion, was reproduced by means of simulations using density functional theory (DFT), enabling the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The major difficulty in studying the hyperfine interactions in SMMs is that, such an effect is quite weak (energy level splitting Δ = 10 -1 ~ 10 0 cm −1 ), so it is easily overwhelmed by large QTMs from dissatisfied coordination environments and/or other inter-metallic magnetic couplings. 46 Therefore until now, only a few well-defined SIMs can serve as suitable platforms to clarify the hyperfine interactions, 4,5,16,17,39,41,[47][48][49][50][51][52] which are usually further accompanied by diamagnetic dilution.…”
Section: Intra-atomic Hyperfine Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The major difficulty in studying the hyperfine interactions in SMMs is that, such an effect is quite weak (energy level splitting Δ = 10 -1 ~ 10 0 cm −1 ), so it is easily overwhelmed by large QTMs from dissatisfied coordination environments and/or other inter-metallic magnetic couplings. 46 Therefore until now, only a few well-defined SIMs can serve as suitable platforms to clarify the hyperfine interactions, 4,5,16,17,39,41,[47][48][49][50][51][52] which are usually further accompanied by diamagnetic dilution.…”
Section: Intra-atomic Hyperfine Couplingmentioning
confidence: 99%
“…From our perspective, the isotopically enriched and magnetically isolated versions of some high-performance Dy SIMs 15 would be nice platforms to further study and clarify the hyperfine interactions in an I ≠0 Dy SIM. In addition, some new techniques should be paid attention to, such as utilizing 161 Dy for time-domain synchrotron Mössbauer spectroscopy 51 and nuclear resonance vibrational spectroscopy 52 to probe the influence of the coordinating ligands as well as the vibration. Moreover, some less-common lanthanide ions, such as 171–174 Yb, 53–55 could also be further studied with regard to the dependence of their magnetic behaviours on the hyperfine interactions.…”
Section: Single-molecule Magnets Beyond a Single Lanthanide Ionmentioning
confidence: 99%
“… [12a] In order to find a clear answer to this, further investigations such as theoretical calculations on the vibrational modes and Dy nuclear resonance vibrational spectroscopy (NRVS) are needed. [21] Furthermore, these investigations could shed light on the vibrational barrier of 14.6 cm −1 seen in ( 2 ) and ( 3 ). It could be clearly shown that acetate in the axial position increases the anisotropy of the system and enhances SMM properties.…”
Section: Discussionmentioning
confidence: 86%
“…For ( 1 ) and ( 2 ) it could also be the result of opening optical phonon processes, as discussed by Gu and Wu, because of the peculiarity of the system with the π‐stacking of the terminal nitrate ligands [12a] . In order to find a clear answer to this, further investigations such as theoretical calculations on the vibrational modes and Dy nuclear resonance vibrational spectroscopy (NRVS) are needed [21] . Furthermore, these investigations could shed light on the vibrational barrier of 14.6 cm −1 seen in ( 2 ) and ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, isotope effects on magnetic relaxation in the research of SMMs are rarely reported. [29][30][31][32][33][34][35][36][37][38][39] Most of them are isotopic enriched or naturally-isotope-pure for the paramagnetic metal centers, like Dy III , Ho III , Er III or Yb III [29][30][31][32][33][34][35][36][37][40][41][42][43][44] clearly revealing that the nuclear spin of the metal center have significant effects on magnetic behavior. However, magnetization dynamics on the diamagnetic coordination ligands are scarcely studied, only two of which were tried to deuterate the ligand and reported the isotope effects.…”
mentioning
confidence: 99%